A Framework for Integrated Risk Management in International Business - Miller, Kent D. (Journal of International Business Studies, 1992)
Treatments of risk in the international management literature largely focus on particular uncertainties to the exclusion of other interrelated uncertainties. This paper develops a framework for categorizing the uncertainties faced by firms operating internationally and outlines both financial and strategic corporate risk management responses.